Seni Lukis Bali Dari Perspektif Modernisasi - I Dewa Putu Merta (Institut Seni Indonesia Denpasar, 2007)
One of the strategic attitudes toward development, in order to increase its improvement by arrangement of comprehensive planning, by considering potency as multi sector development concept is the development of art that is taken for consideration. The development of art in Bali nowadays is closely related to the historic movement of Indonesian art, pioneering era Raden Saleh (1807-1880), Hindia Jelita era (1908-1937), and Pita Maha era (1930s). In the Pita Maha era, there occurred a combinatioan between the modern west esthetic and classical Bali esthetic that based on Hindu religion. The modern esthetic was brought to Bali by western artist R. Bonnet and W. Spiese, merging with the classical esthetic which bearing aperiod of art in Bali that is known as Seni Lukis Bali Modern (Bali Modern Art Painting) The period is also the beginning of Modern Art in Bali. Academic movement in the field of art exist in 1950 is an attitude toward renewal expansion within expression. During the orde baru government in 1966, various styles of modern art come into elaboration, moreover by the graduations of many academic artists.